New Directions For Foster Care Reform. (March 2017) - Wald, Michael S.
Abstract: Since the 1970s, legislatures and courts have adopted a variety of approaches to address foster care's overuse, instability, and lack of permanence. Most reforms focused on rules and procedures. It appears that there has been progress with respect to each of these issues, but the foster care system still has many deficiencies. It is unlikely that further changes in legal standards will significantly improve the system; the core issues relate to implementation of good practices. The foster care system now responds to three types of problems: protecting children from parental maltreatment; helping children who exhibit severe behavioral problems; and dealing with families experiencing high levels of parent‐child conflict. Services should be redesigned to reflect differences in the issues presented by the three populations.